THE ROLE OF LEADERS IN GIVING SANCTIONS FOR DISCIPLINE VIOLATIONS TO STATE CIVIL APPARATUS (ASN) AT THE ACEH ENERGY AND MINERAL RESOURCES SERVICE (ESDM) - Nurliana; Taufik; Ellyana, Cut Putri (Dinasti Publisher, 2022)
There are still many ASN who do not understand the provisions of government regulations. The problem of indiscipline of civil servants is a topic of discussion for the public in general. In addition to performance that is often considered less than optimal, the ASN discipline factor also often receives sharp criticism from the public. Problem formulation: How is leadership development at the Aceh Energy and Mineral Resources (ESDM) Service? How is the application of sanctions for ASN disciplinary violations at the Aceh Energy and Mineral Resources (ESDM) Service? This study uses a qualitative approach and data collection techniques are carried out using observation, interview and documentation study techniques. The results of this study indicate that in the general section of the Aceh Energy and Mineral Resources (ESDM) Service, the implementation of state civil apparatus discipline is still not optimal due to several factors, namely that there are still violations committed by civil servants such as rarely attending roll calls, arriving late, being outside the office during office hours, and so on. This study aims to determine how the implementation of state civil apparatus discipline is in the general section of the Aceh Energy and Mineral Resources (ESDM) Service, and how successful the implementation of state civil apparatus discipline is in the general section of the Aceh Energy and Mineral Resources (ESDM) Service. This study uses a qualitative approach and the type of research is descriptive. Data collection techniques were carried out by interview, observation and documentation. The results of the study showed that the implementation of civil servant discipline in the general section of the Aceh Energy and Mineral Resources Service has not been fully successful, because there are still employees who commit violations, namely lack of awareness in implementing the rules, lack of supervision, and lack of strict sanctions given to violators at the Aceh Energy and Mineral Resources Service. Therefore, awareness is needed from each individual to obey and comply with the rules, strict sanctions are needed if an ASN is proven to have committed a violation with the aim of providing a deterrent effect and not repeating the same mistake in the future. In conclusion, employees who work not in accordance with their educational background will be guided, fostered and directed. The leader will provide training to these employees so that they can work in accordance with the main tasks and functions given. The implementation of ASN discipline at the ESDM Service has been implemented with Government Regulations. In its implementation, there are still frequent violations of discipline in the general section, especially in terms of timekeeping, there are still many employees who do not arrive on time.